Equitably Assessing the Weight of Non-Monetary Contributions in Kenya (Strathmore Law Review, 2023)
Article 45 of the Constitution of Kenya establishes the family as the natural and fundamental unit of the society. Marriage is one of the main ways of creating a family, and the spouses in such a marriage are deemed to have equal rights. Upon the dissolution of the marital union, the spouses are faced with the challenge of dividing the property they acquired during their union. In this division, courts have taken opposing stances. One faction advocates for the equal division of property based on the fact that the spouses have equal rights. Another faction claims that marital property should be distributed on the basis of contribution since equality of rights does not necessarily translate to equal division of property. Consequently, the value of monetary and non-monetary contributions becomes increasingly important when dividing matrimonial property. Unfortunately, non-monetary contributions have historically been left out up until the enactment of the Matrimonial Property Act of 2014. Even then, in the eyes of judicial officers, non-monetary contribution appears to be a lesser consideration given the ease of proving monetary contributions. Using a doctrinal analysis, this paper argues that non-monetary contribution is not accorded the same consideration as monetary contributions, which goes against the constitutional standard of equity. It is suggested that an application of a mathematical formula can remedy this inequity by placing each of the contributions on the same footing when dividing matrimonial property.